Isotretinoin-associated pseudoporphyria. - Riordan, C; Anstey, A; Wojnarowska, F (1993)
We present two patients who developed pseudoporphyria whilst taking isotretinoin (Roaccutane). At that time, both patients were receiving other agents which could be incriminated as causing their pseudoporphyria. However, it is significant that these other agents had been longstanding and that the porphyria-like cutaneous changes did not develop until after the introduction of the isotretinoin (Roaccutane). In both cases, withdrawal of the isotretinoin resulted in clinical improvement of their cutaneous signs. The interaction of isotretinoin and another agent, rather than isotretinoin independently, may be involved in the development of pseudoporphyria.